2022
DOI: 10.1021/acs.inorgchem.2c01226
|View full text |Cite
|
Sign up to set email alerts
|

In Situ X-ray Diffraction Studies on the Production Process of Molybdenum

Abstract: During the production of molybdenum, the first reduction step of molybdenum trioxide to molybdenum dioxide is crucial in directing important product properties like particle size and oxygen content. In this study, the influence of heating rate, hydrogen flow, and potassium content on the reduction of MoO3 has been investigated via in situ X-ray powder diffraction. For low heating rates, a molybdenum bronze H x MoO3 could be confirmed as an intermediate, while γ-Mo4O11 can only be observed at high heating rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 26 publications
(49 reference statements)
0
11
0
Order By: Relevance
“…[26,27] Even though the reduction of V 2 O 5 and WO 3 have been thoroughly studied by means of ex situ X-ray diffraction, [6,23,28] neither process has been investigated by in situ X-ray diffraction, yet. Similar studies that have been performed on the reduction of other transition metal oxides with hydrogen, like MoO 3 , [29][30][31][32] improved the understanding of these reactions by clarifying the influence of additives on the reaction and revealing intermediates as well as explaining their formation in the context of reaction conditions. Therefore, in this contribution, we use this concept to investigate the reduction of WO 3 and V 2 O 5 by hydrogen with regards to intermediates and influences of the heating rate.…”
Section: Introductionmentioning
confidence: 71%
“…[26,27] Even though the reduction of V 2 O 5 and WO 3 have been thoroughly studied by means of ex situ X-ray diffraction, [6,23,28] neither process has been investigated by in situ X-ray diffraction, yet. Similar studies that have been performed on the reduction of other transition metal oxides with hydrogen, like MoO 3 , [29][30][31][32] improved the understanding of these reactions by clarifying the influence of additives on the reaction and revealing intermediates as well as explaining their formation in the context of reaction conditions. Therefore, in this contribution, we use this concept to investigate the reduction of WO 3 and V 2 O 5 by hydrogen with regards to intermediates and influences of the heating rate.…”
Section: Introductionmentioning
confidence: 71%
“…[16] In previous contributions we use the concept of in situ characterization techniques to investigate the occurrence of intermediates in the reduction of molybdenum oxide and to explain different reaction pathways depending on heating rate and hydrogen gas flow. [19] Such rational approaches to solidstate synthesis planning like the investigation of reaction pathways by in situ methods [20] are rarely applied to industrial processes, but can yield very valuable information on the effect of process parameters on the products. Furthermore, they may help controlling product properties, avoiding unwanted byproducts and optimizing reaction conditions and energy consumption.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that an orthorhombic molybdenum bronze H x MoO 3 occurs as an intermediate of the reduction of MoO 3 at low heating rates while Mo 4 O 11 can only be observed at higher rates. [19] High hydrogen flow rates favor the formation of molybdenum at lower temperatures. Furthermore, the content of potassium as an additive in MoO 3 in the industrial process influences the amount of Mo 4 O 11 formed during the reduction as well as the time it takes to form Mo 4 O 11 and MoO 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11,12] Time-resolved analytical techniques can be used to follow chemical reactions of solids and can uncover reaction pathways as well as provide information on the dynamics, making them a welcome extension of the otherwise often static picture of solids in industrial processes. [13,14] The production process of rhenium has not been thoroughly studied by means of in situ X-ray diffraction yet, but similar studies that have been performed on other refractory metals produced via reduction with hydrogen, like molybdenum, [15][16][17][18] delivered promising results by revealing intermediates, explaining their formation in the context of ambient conditions and clarifying the influence of additives on the reaction. Therefore, in this contribution, we use this concept to investigate the reduction of ammonium perrhenate with regards to intermediates and influences of the gas atmosphere.…”
Section: Introductionmentioning
confidence: 99%